So you want to talk about race [compact disc, unabridged] - Oluo, Ijeoma (Blackstone Audio, Inc., 2018)
A current, constructive, and actionable exploration of today's racial landscape, offering straightforward clarity that listeners of all races need to contribute to the dismantling of the racial divide.